Some biological aspects of indian mackerel (Rastelliger kanagurta Cuvier, 1817) in Bali Strait waters - Parawangsa, I Nyoman Yoga; Tampubolon, Prawira Atmaja (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2023)
Indian mackerel (Rastrelliger kanagurta Cuvier, 1817) is a small pelagic fish species which is the main catch commodity in purse seine and jukung fleets in the Bali Strait waters. Sustainable management is urgently needed for indian mackerel populations in Bali Strait waters to remain sustainable fishery. The availability of basic information such as biological aspects is very important as a fundamental resource in the management of indian mackerel in Bali Strait waters. The aims of this study were to reveal several biological aspects of mackerel such as growth patterns, condition factors, sex ratio, and size at first maturity of indian mackerel in Bali Strait waters. Sampling was carried out in May-September 2018. Samples of fish were taken from purse seine and jukung fleets using trawl nets and gill nets. Fish sample was measured, weighed and dissected to observe the sex and the gonadal maturity stage. The total number of indian mackerel samples was 167 individuals. Mackerel in the Bali Strait waters has a positive allometric growth pattern with fish in good condition. The sex ratio was in an unbalanced condition with the number of male fish being more than the female fish. The size at first maturity was 19.34 cm for male fish and 19.76 cm for female fish.